Impact of different types of revision materials on the learning of musculoskeletal techniques. (March 2021) - Launay, François; Ménard, Mathieu; Bourgin, Marylène; Mhadhbi, Hakim; Sutre, Franck; Draper-Rodi, Jerry
Abstract: Background: This study aimed to measure the impact of different revision materials developed for osteopathy students, by studying their results, their perceptions and their behaviour when revising for exams. Methods: A cohort of 68 second-year osteopathic students was allocated to three groups (pseudo-randomisation), each group being separately taught the same practical course, but provided with different types of revision materials (video, digital data sheet or no material). They were then assessed by an external examiner. Outcome measures were grades, time spent revising on the platform and student material perceptions collected via a practical assessment, by monitoring student visits on an education platform (Tactiléo®) and a questionnaire. Results: The results showed that the mean exam grades for the Video group were 14% higher than those of the No Materials group (p = 0.04, d = 0.94) and 29% higher than the Digital Data Sheet group (p < 0.01, d = 1.36). In addition, an interesting result was that students from the Video group spent more time using the revision materials (+29%), consulted them more often (+25%) and repeated their techniques more often than students in the Digital Data Sheet group (+14%). Conclusions: The use of video revision material improved participants' results while exerting a positive influence on their behaviour when revising but did not prevent surface learning. A structured teaching and learning approach will therefore need to be implemented if learners are to get all the benefits of video materials while being more engaged on a personal level.